The Diversity and Density of the Population Parasitoid who Associated with Plutella xylostella L. (Lepidoptera: Plutellidae) on Plantation Plants without and with Insecticide Application - NI PUTU ESA YANTI SUPARTHA; I WAYAN SUSILA; KETUT AYU YULIADHI (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology))
ABSTRACT The Diversity and Density of the Population Parasitoid who Associated with Plutella xylostella L. (Lepidoptera: Plutellidae) on Plantation Plants without and with Insecticide Application The research was conducted at the Laboratory of Integrated Pest and Disease  Management, Concentration of Plant Protection, Department of Agroecotechnology, Faculty of Agriculture Udayana University. The purpose of this research to find out diversity and density of parasitoids population associated with  Plutella xylostella on cabbage plantation without and with insecticide application. Sample was taken by using diagonal sampling. There are nine points sample on cabbage plantation without and with insecticide application and each point content 18 plants. The sample was taken every weeks, while application insecticide was done every 10 days. Data was analyzed by using T-test. The result of the research indicated that there is one parasitoid was found associated with P. xylostella on cabbage plantation without and with insecticide application. That parasitoid is Diadegma semiclausum. Population of P. xylostella and D. semiclausum not significant difference on cabbage plantation without and with insecticide application, and so it seems of parasitization rate of parasitoid.   Keywords: insecticide, Plutella xylostella, parasitoid, cabbage